Sharing Personal Experiences of Accessibility and Knowledge of Violence: A Qualitative Study. Issue 3 (February 2022) - Mantler, Tara; Jackson, Kimberley T.; Walsh, Edmund J.; Tobah, Selma; Shillington, Katie; Jackson, Brianna; Soares, Emily
In North America, the most common societal response to intimate partner violence (IPV) has been the establishment of women's shelters for temporary housing and security. Rurality further compounds the challenges women experiencing IPV face, with unique barriers from their urban counterparts. This study sought to explore the intersection of rural women's health care experiences within the context of IPV. Eight rural women living in Southwestern Ontario, who had experienced IPV, had used women's shelter services, and who had accessed health care services in the preceding 6 months were interviewed. Using a feminist, intersectional lens, we collected and analyzed qualitative data using an interpretive description approach. Findings demonstrated that women were able to identify strengths and opportunities from their experiences, but significant challenges also exist for rural women seeking health care who experience IPV. Our findings underscore the need for filling of policy gaps between health care and the services women use. We propose that further research is needed on alternative, integrated models of shelter services that address health care needs for women experiencing IPV.